2013
DOI: 10.1007/s00210-013-0841-8
|View full text |Cite
|
Sign up to set email alerts
|

Predominant role of the dopamine D3 receptor subtype for mediating the quinpirole-induced inhibition of the vasopressor sympathetic outflow in pithed rats

Abstract: We have recently reported that quinpirole (a D2-like receptor agonist) inhibits the vasopressor sympathetic outflow in pithed rats via sympatho-inhibitory D2-like receptors. Since D2-like receptors consist of D2, D3 and D4 receptor subtypes, this study investigated whether these subtypes are involved in the above quinpirole-induced sympatho-inhibition by using antagonists of these receptor subtypes. One hundred fifty-six male Wistar rats were pithed and prepared for preganglionic spinal (T7-T9) stimulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 33 publications
4
28
1
Order By: Relevance
“…Nevertheless, Ruiz‐Salinas et al . () showed in pithed rats that the same highest doses of SB‐277011‐A and L‐745,870 abolished and weakly blocked, respectively, quinpirole‐induced inhibition of the vasopressor sympathetic outflow.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, Ruiz‐Salinas et al . () showed in pithed rats that the same highest doses of SB‐277011‐A and L‐745,870 abolished and weakly blocked, respectively, quinpirole‐induced inhibition of the vasopressor sympathetic outflow.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ruiz‐Salinas et al . () have shown, using the same compounds, same doses, same i.v. routes and same species as in our present investigation, that quinpirole‐induced inhibition of the vasopressor sympathetic outflow resembles the pharmacological profile of the D 3 receptor subtype and, to a lesser extent, of the D 4 receptor subtype, with no evidence for the role of the D 2 subtype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, further experiments using selective antagonists, which fall beyond the scope of the present investigation, will be required to identify the D 2/3/4 subtype involved in the sympatho-inhibition to ergotamine. In this sense, it has been reported that D 3 and D 4 subtypes are predominantly involved in the sympatho-inhibition of the vasopressor sympathetic outflow to quinpirole (Ruiz-Salinas et al, 2013). Consistent with our results, previous studies have demonstrated that ergotamine-induced vascular sympathoinhibition was blocked by yohimbine (α 2 -adrenoceptor antagonist) and sulpiride (D 1/2 -like antagonist) (Badia et al, 1988) and the cardiac sympatho-inhibition to ergotamine is blockade by rauwolscine (α 2 -adrenoceptor antagonist) and haloperidol (D 1/2 -like antagonist) (Cobos-Puc et al, 2009) suggesting that the α 2 -adrenoceptors and also D 2 -like receptors are involved.…”
Section: Way 100635 + Ergotamine Gr 127935 + Ergotaminementioning
confidence: 97%